PENGARUH FAKTOR INTERNAL BANK TERHADAP JUMLAH KREDIT YANG DISALURKAN (Studi empiris pada bank yang terdaftar di Bursa Efek Indonesia) - Yuda, I Made Pratista; Meiranto, Wahyu (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2010)
Providing funds (lending) in the form of credit is an activity that dominates the banking businessin its function as an intermediary institution. Performance of the banking industry-improvedresults with increasing intermediation role and has improved bank profitability. This study aimedto examine the effect of bank internal factors (third party funds obtained from the public, capitaladequacy ratio, return on assets and non-performing loans) to outstanding loans. The samples inthis study were the banks listed on the Indonesia Stock Exchange from 2006 to 2009. The data willbe analyzed by multiple regression. The analysis technique used to test the research hypotheseswere the F test and t test with a significant level of 5%. The results of this study indicate that thethird-party funds have a positive effect on lending, capital adequacy ratio has a negative effecton lending, return on assets has a positive effect on on lending. Non-performing loans have anegative effect on lending. From the analysis it can be concluded that the third-party funds,adequecy capital ratio, return on assets and non-performing loans have an effect simultaneouslyto outstanding loans.